The opinion of various groups within the Faculty of Health Sciences at the University of the Witwatersrand regarding the use of the newly deceased for life saving skills competency training - Kramer, Efraim Benjamin (My University, 2014)
Society expects that all on duty emergency department personnel will be competent in life saving medical procedures so as to adequately and appropriately resuscitate and stabilise the acutely ill or injured who may present for treatment. For competence to exist, the relevant medical skills have to be initially acquired and thereafter maintained, which necessitates sufficient training. This research report set out to gauge the opinions of various undergraduate and postgraduate groups within the Faculty of Health Sciences of the University of the Witwatersrand regarding the use of the newly deceased for life saving skills competency training, with or without surviving family permission. It also sought to ascertain whether use of the newly deceased was being practiced, and if so, with or without family permission.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfillment of the degree of Master of Science in Medicine in Bioethics and Health Law. Johannesburg, January 2012
Keywords: Surveys and Questionnaires